2011
DOI: 10.1111/j.1439-0388.2011.00976.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic parameters for energy balance, fat /protein ratio, body condition score and disease traits in German Holstein cows

Abstract: Various health problems in dairy cows have been related to the magnitude and duration of the energy deficit post partum. Energy balance indicator traits like fat/protein ratio in milk and body condition score could be used in selection programmes to help predicting breeding values for health traits, but currently there is a lack of appropriate genetic parameters. Therefore, genetic correlations among energy balance, fat/protein ratio, and body condition score, and mastitis, claw and leg diseases, and metabolic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
48
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(58 citation statements)
references
References 36 publications
8
48
0
2
Order By: Relevance
“…Within the fact that F/P ratio can be observed at any test-day its estimation doesn't increase cost of production. Presented results are in concordance with Buttchereit et al (2012), who reported that F/P ratio and body condition score are potential variables to describe how well cows can adapt to the challenge of early lactation. Similarly, Heuer et al (1999) reported that first test-day milk yield and first test-day F/P ratio were more reliable indicators of metabolic disease, other lactation diseases, fertility, milk yield and culling than were first body condition scores (BCS) postpartum or body condition loss from the first to second scoring.…”
Section: Discussionsupporting
confidence: 79%
“…Within the fact that F/P ratio can be observed at any test-day its estimation doesn't increase cost of production. Presented results are in concordance with Buttchereit et al (2012), who reported that F/P ratio and body condition score are potential variables to describe how well cows can adapt to the challenge of early lactation. Similarly, Heuer et al (1999) reported that first test-day milk yield and first test-day F/P ratio were more reliable indicators of metabolic disease, other lactation diseases, fertility, milk yield and culling than were first body condition scores (BCS) postpartum or body condition loss from the first to second scoring.…”
Section: Discussionsupporting
confidence: 79%
“…Nevertheless attention should still be paid to F/P and the incorporation of fat-toprotein ratio into breeding programs should be considered. As noted by Buttchereit et al (2012), improvement in the overall health of dairy cattle can be expected if energy balance traits are included into breeding programs. F/P can be quite easily combined with BCS.…”
Section: Genetic Correlationsmentioning
confidence: 99%
“…In their study of 1693 Holstein cows in Germany Buttchereit et al (2012) estimated a heritability of F/P of 0.30 ± 0.05. So it can be stated that F/P is a relatively highly heritable trait.…”
Section: Heritabilitymentioning
confidence: 99%
See 2 more Smart Citations